Integrated networks of health services: towards the construction of a concept - Riaño Casallas, Martha Isabel; Martínez, Magda (Universidad y Salud, 2012)
This reflective article presents in detail a conceptual framework that seeks to expose the different concepts related to Integrated Networks of Health Services (INHS). For this purpose, the basic definition of network, health networks and integrated health care organizations proposed by various authors as well as the experiences in the operation of networks in Europe, mainly in Spain and some Latin American countries were reviewed.